2021
DOI: 10.1186/s13063-021-05414-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moderate-intensity intermittent hypoxic training on health outcomes of patients recovered from COVID-19: the AEROBICOVID study protocol for a randomized controlled trial

Abstract: Background Recent studies point to a lower number and reduced severity of cases in higher altitude cities with decreased oxygen concentration. Specific literature has shown several benefits of physical training, so, in this sense, physical training with hypoxic stimulus appears as an alternative that supports the conventional treatments of the COVID-19 patient’s recovery. Thus, this study’s primary aim is to analyze the effects of moderate-intensity intermittent hypoxic training on health outco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…The underlying systemic inflammation contributes to muscle atrophy indirectly (lung obstruction and forced inactivity) or directly (increased muscle wasting, necrosis, fibrosis and autophagy, and mitochondrial dysfunction), while viral antigen mimicry might cause muscle denervation in peripheral nerves. While physical activity (PA) has been identified as a predictive and protective factor against severe forms of COVID-19 [ 17 , 18 , 19 , 20 ], it has also been suggested as a key factor for rehabilitation [ 21 , 22 , 23 ], both for the acute and long-term consequences of this new global disease. According to a survey questioning the specific rehabilitation needs reported by post-COVID-19 patients themselves [ 24 ], exercise guidance appears to be a primary concern.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying systemic inflammation contributes to muscle atrophy indirectly (lung obstruction and forced inactivity) or directly (increased muscle wasting, necrosis, fibrosis and autophagy, and mitochondrial dysfunction), while viral antigen mimicry might cause muscle denervation in peripheral nerves. While physical activity (PA) has been identified as a predictive and protective factor against severe forms of COVID-19 [ 17 , 18 , 19 , 20 ], it has also been suggested as a key factor for rehabilitation [ 21 , 22 , 23 ], both for the acute and long-term consequences of this new global disease. According to a survey questioning the specific rehabilitation needs reported by post-COVID-19 patients themselves [ 24 ], exercise guidance appears to be a primary concern.…”
Section: Introductionmentioning
confidence: 99%
“…The present study follows the work of the AEROBICOVID project, a clinical trial controlled double-blind study were performed between September and December 2020, and details could be found elsewhere ( Trapé et al, 2021 ). Participants aged 30–69 years and COVID-19 convalescents (with a positive diagnostic test) who had symptoms approximately 30 days since recovery from clinical signs or medical discharge were included.…”
Section: Methodsmentioning
confidence: 99%
“…The research experimental setup included two tents (Colorado Altitude Training Tent™, United States), with 12,000 L of air capacity, and a hypoxia generator (CAT-430™, Altitude Control Technologies, United States) for each tent ( Trapé et al, 2021 ). There were participants from all three training groups around the tents and individual hoses directed towards the tent, all being covered by a tarp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the developing COVID-19 pandemic, application of IHT for treatment of patients during the rehabilitation period has been considered as a beneficial option. The assessment of the effects of moderate-intensity IHT on health outcomes in patients recovering from COVID-19 is now under trial ( Trapé et al, 2021 ).…”
Section: The Therapeutic Potential Of Hypoxic Trainingmentioning
confidence: 99%